2016
DOI: 10.4236/ijohns.2016.53019
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cervicofacial Cellulitis Supported in University Hospital Yalgado Ouedraogo

Abstract: Introduction: The complications of cervicofacial cellulitis are one of the most serious emergencies Oto-Rhino-Laryngology (ORL). These complications are still observed in our context despite the advent of antibiotics. The aim of our study was to describe the clinical presentation and management of patients admitted to our institution for complications of cervicofacial cellulitis. Patients and Methods: It came from a retrospective study in the ORL service, a department of Yalgado Ouédraogo Hospital of Ouagadoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…ey were observed in our series when the treatment was not respected and was the cause of death in 4.44% of cases. ey compromise the prognosis of the patient and increase the demand for monitoring in an intensive care unit [20]. e unsightly scars were observed in cases of necrosis with tissue loss and were associated with a poor aesthetic prognosis in 13.33% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…ey were observed in our series when the treatment was not respected and was the cause of death in 4.44% of cases. ey compromise the prognosis of the patient and increase the demand for monitoring in an intensive care unit [20]. e unsightly scars were observed in cases of necrosis with tissue loss and were associated with a poor aesthetic prognosis in 13.33% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Nigeria found cervicofacial infection to be one of the leading causes of death in a maxillofacial unit, accounting for about 41.3% of maxillofacial mortality over a 10 years period ( 7 ). Other reported incidences of mortality in developing countries are 17.4% in Burkina-Faso ( 9 ), 5.8% in Ghana ( 10 ) and 0.8% in China ( 11 ). Generally, a higher incidence of cervicofacial infection and mortality rate has been reported in developing countries and this has been attributed to malnutrition, late presentation and poor health services ( 7 ).…”
Section: Introductionmentioning
confidence: 99%